ANALISIS KELEMBAGAAN DAN EFEK BERGANDA ZAKAT MAAL DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT - Chotib; Sutomo; Hery Yuswadi; Ahmad Toha (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2016)
Zakat is a means to drain wealth from the rich to the poor. Paying zakat in Islam is obligatory for a Muslim who qualified for charity. Nevertheless, there are still many who do not carry out these obligations. Zakat is a method to increase the prosperity of the people, for it is in this study will be presented multiplier effect zakat maal in improving people's welfare. This study is a qualitative study with Interpretative Phenomenological Analysis method through six stages of analysis: 1) Reading and Re-reading; 2) Initial noting; 3) Developing Emergent Themes; 4) Searching for connection across emergent themes; 5) Moving the next cases; and 6) Looking for patterns across cases. Which would then be quantified into economic mathematical logic. As a result, the use of zakat productively with good mentoring, It will increase welfare. Economically, there will be further flow of venture capital can be to be played in productive activities, the impact will increase people's incomes.